Performance Anxiety during Exams: Predictors of Students’ Academic Failure (Journal of Social Sciences Review, 2023)
While the concept of student’s performance anxiety has received considerable attention in different branches of the social science literature, the factors of performance anxiety have been somewhat neglected, particularly with respect to the educational sector. Motivated by the need to further explore this concept, this paper empirically investigates the predictors of students’ academic failure and the mediating role of performance anxiety during exams. In the current research, researchers examined the effect of students' fear of results, lack of preparation, past experiences of failure, and cognitive inattention on academic failure via mediating role of performance anxiety between independent and outcome variables. The sample size consists of 502 students from renowned public universities in Pakistan. Data is collected from respondents using a self-administered questionnaire by utilizing a stratified sampling technique.  The outcome of this study revealed that predictors have a direct and significant impact on the academic failure of students.  The results of this study imply that students’ performance anxiety has a significant mediating role between predictors of students’ academic failure on academic failure. All in all, this research makes a unique contribution to university instructors since it gives information on the prospects for exam anxiety and helps them understand and sort out the issues that
Keywords: Academic Failure; Performance Anxiety; Fear of Results; Lack of Preparatio; Past Experience of Failure; Academic Failure, Performance Anxiety, Fear of Results, Lack of Preparation, Past Experience of Failure and Cognitive Inattention